A U.S. Pharmacopeia (USP) overview of Pan American botanicals used in dietary supplements and herbal medicines - Upton, Roy; Agudelo, Ignacio; Cabrera, Yadira; Caceres, Armando; Calderón, Angela; Calzada, Fernando; Camacho, Rosa; da Costa, Fernando; Dobrecky, Cecilia; Enciso, Roberto; Escobar, Marcela; Fakhary, Mina; et al. (Frontiers in Pharmacology, 2024)
The United States Pharmacopeial Convention (USP) is a nonprofit, scientific, standard-setting organization, and world leader in establishing quality, purity, and testing standards for medicines, foods, and dietary supplements. USP quality standards are used in more than 140 countries and are legally recognized by more than 40 countries. Currently, there is renewed interest in herbal medicines globally, and health policies are being implemented worldwide for the use of complementary and traditional medicine. In response, USP has developed a robust body of monographs that can be used to guide industry and regulators in ensuring the quality and safety of botanical ingredients used in dietary supplements and herbal medicines. Throughout the Pan American regions, there is a strong tradition of using botanicals as herbal medicines and, as in other regions, a growing desire for botanical dietary supplements. This underscores the need for public quality standards to ensure quality, reduce the flow of substandard and adulterated products, and ensure public health and safety. In April 2022, USP launched the Pan America Botanical Dietary Supplements and Herbal Medicines Expert Panel, with experts representing 12 different countries. The Expert Panel's work focuses on developing quality control standards for the most important botanical ingredients used in the respective countries, ingredients that are also of global importance. This article provides an overview of the state of botanical dietary supplements and herbal medicines in different Pan American regions with a focus on the regulatory status of herbal products, the development of national quality and research initiatives, and policies related to agriculture conservation and sustainability, among other topics.Pharmacopeias are officially recognized sources of quality standards for identity, strength, purity, and limits of contaminants for ingredients and preparations used as medicines. Until approximately the 1930s, the majority of medicines formally accepted in medical practice throughout most of the world were derived from botanical ingredients. These medicines comprised a mix of crude Galenical preparations (teas, pills, tinctures, syrups, etc.) and substances isolated from plants (e.g., digitalis glycosides). Even today, the majority of the global population utilizes